Współczesne koncepcje doskonalenia jakości informacji - Chomiak-Orsa, Iwona; Gryncewicz, Wiesława (Modern Conceptions of Information Quality Management, 2007)
The aim of this article is to present the most important modem conceptions of information quality management. These are:- Total Information Quality Management Methodology of L. English,- Algorithm of Information Quality Improvement of B. Godfrey,- Data Quality Program of D. Loshin,- Data Quality Program of PricewaterhouseCoopers,- Data Quality Program of J. Geiger.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 113-124